Contemporary development issues in Nigeria - Akinsanya, A. A. (Ibadan : University of Ibadan, 1989)
This is a report of the National Workshop organised by the social science council of Nigeria in collaboration with the Ford Foundation at the Faculty of the Social Sciences, University of Ibadan, Ibadan, September 18-19, 1989.
lje 11/12/18
Loans
Keywords: Research Methods; Development; Nigeria